The key role of exudative lesions and their encapsulation: lessons learned from the pathology of human pulmonary tuberculosis - Cardona, Pere-Joan (Frontiers in Microbiology, 2015)
A review of the pathology of human pulmonary TB cases at different stages of evolution in the pre-antibiotic era suggests that neutrophils play an instrumental role in the progression towards active TB. This progression is determined by the type of lesion generated. Thus exudative lesions, in which neutrophils are the major cell type, are both triggered by and induce local high bacillary load, and tend to enlarge and progress towards liquefaction and cavitation. In contrast, proliferative lesions are triggered by low bacillary loads, mainly comprise epithelioid cells and fibroblasts and tend to fibrose, encapsulate and calcify, thus controlling the infection. Infection of the upper lobes is key to the progression towards active TB for two main reasons, namely poor breathing amplitude, which allows local bacillary accumulation, and the high mechanical stress to which the interlobular septae (which enclose secondary lobes) are submitted, which hampers their ability to encapsulate lesions. Overall, progressing factors can be defined as internal (exudative lesion, local bronchogenous dissemination, coalescence of lesions), with lympho-haematological dissemination playing a very limited role, or external (exogenous reinfection). Abrogating factors include control of the bacillary load and the local encapsulation process, as directed by interlobular septae. The age and extent of disease depend on the quality and speed with which lesions liquefy and disseminate bronchially, the volume of the slough, and the amount and distribution of the sloughing debris dispersed.